Solve the systems of equations using elimination.
Check your solution by solution it back into the system.
1. 2x - 3y = -4
4x + 3y = 10

HELPPP

Respuesta :

Answer:

(1, 2 )

Step-by-step explanation:

2x - 3y = - 4 → (1)

4x + 3y = 10 → (2)

Since the y-terms are opposites then adding the equations term by term will eliminate them.

6x = 6 ( divide both sides by 6 )

x = 1

Substitute x = 1 into either of the 2 equations and solve for y

Substituting into (2)

4(1) + 3y = 10

4 + 3y = 10 ( subtract 4 from both sides )

3y = 6 ( divide both sides by 3 )

y = 2

solution is (1, 2 )